PERENCANAAN ULANG SISTEM INSTALASIAIR BERSIH KANTOR OTORITAS BANDAR UDARA WILAYAH III - Martini, Ninik; ., Sudarmono (MEKANIKA: Jurnal Teknik Mesin, 2015)
Redesign Water System Intallation Office of Airport Authority Region III. Old building and new buildingAirport Authority Region III has a working installation of water and pumps of different systems. Old buildingconsists of three floors using press tank system (hydrosphere). Being new building consists of 7 floors using rooftank systems. With consideration of cost efficiency of electricity consumption and maintenance costs burden, thepress tank system is considered less efficient because of the fluctuation of the working pressure greater than the tankroof system. This resulted in the pumps often operate ON - OFF quickly also resulting in large power consumptionand potentially cause damage to pumps and installation. The purpose of this study was to plan the installation of thesystem on integrated water on both the building using roof tank system. From the analysis of the water requirementcalculations required water availability of 120 m3 / day. For office buildings with average working hours of eighthours are taken into account during peak usage hours by 27 m3 / h. Of the allowable flow rate, then the dimensionsof the transfer pipes and main pipes  3 inch, collection pipes and branch pipes varies the  ½, ¾, 1, 1¼ and 1½ inch. For ground water tank volume of 90 m3, roof tank was needed capacity of 67.5 m3 (3 units @ 22,500 litertank). Take into account head losses that occur in the transfer pipe, acquired 34 m total head pumps, hydraulicpower with 78% efficiency of 3.21 kW. Of reference brands Grundfos pump then pumps Grundfos selected types ofvertical multistage centrifugal pump with specifications: Type CR (E) 32-2, capacity 32 m3 / h, head 34 m, 4 kWmotor power, supply voltage 3 x 380-480 Volt, 2900 rpm rotation and frequency of 50 Hz. Pumps installed two unitsin parallel.Keywords: the water demand, roof tank, pump, flow rate, reservoir.